2016
DOI: 10.1089/jop.2015.0121
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Forskolin, Homotaurine, Carnosine, and Folic Acid in Patients with Primary Open Angle Glaucoma: Changes in Intraocular Pressure, Pattern Electroretinogram Amplitude, and Foveal Sensitivity

Abstract: The results of the present pilot study indicate that the components of the food supplement reach the eye in a detectable manner, as evidenced by the effects on the IOP. Moreover, they suggest a short-term neuroactive effect, as indicated by the improvement of PERG amplitude and foveal sensitivity in treated, but not in control patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…For instance, forskolin has been reported to act synergistically with homotaurine to protect RGC from death induced by increased IOP possibly by preventing calpain activation that is associated to neurodegenerative events [34]. In addition, in glaucoma patients with IOP compensated by topical drugs, food supplements containing forskolin, homotaurine, and group B vitamins have been found to increase both PERG amplitude and additional parameters related to RGC function [35]. Overall, literature data indicating the possible synergy between the different bioactive components of Gangliomix suggest that no single constituting element may have, per se, a neuroprotective activity comparable to that of the entire compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, forskolin has been reported to act synergistically with homotaurine to protect RGC from death induced by increased IOP possibly by preventing calpain activation that is associated to neurodegenerative events [34]. In addition, in glaucoma patients with IOP compensated by topical drugs, food supplements containing forskolin, homotaurine, and group B vitamins have been found to increase both PERG amplitude and additional parameters related to RGC function [35]. Overall, literature data indicating the possible synergy between the different bioactive components of Gangliomix suggest that no single constituting element may have, per se, a neuroprotective activity comparable to that of the entire compound.…”
Section: Discussionmentioning
confidence: 99%
“…This amount of Gangliomix corresponds to 86.7 mg of a dry extract of spearmint (containing 20.9 mg of total polyphenols and 12.6 mg of rosmarinic acid) designated as Neumentix, 19.3 mg of dry extract of Coleus forskohlii (titrated at 10% in forskolin), 14.5 mg of homotaurine, 2.7 mg of vitamin PP, 0.4 mg of vitamin B2, 0.4 mg of vitamin B6, 0.3 mg of vitamin B1, and 0.5 mg of vitamin B12. Neumentix, which is rich in polyphenols and rosmarinic acid, is believed to be most beneficial for cognitive support by providing neurons with trophic supply [33] while the additional components of Gangliomix are also known to play a neuroprotective role [34,35].…”
Section: Dietary Supplementationmentioning
confidence: 99%
“…Although more than one mechanism might account these synergistic properties, this neuroprotection was associated with reduced calpain activity, upregulation of the phosphoinositide 3-kinase (PI3K)/Akt pathway, and inhibition of glycogen synthase kinase-3 β (GSK-3 β ). Moreover, a recent pilot study demonstrated that oral administration of homotaurine, forskolin, carnosine, and folic acid improves intraocular pressure in patients with primary open-angle glaucoma [ 38 ]. Therefore, a multitarget approach by using a combination of molecules may be a more promising strategy to prevent retinal degeneration or slow down glaucomatous progression.…”
Section: Discussionmentioning
confidence: 99%
“…e dosage change to a single tablet after 60 days showed a slight reduction in the effects on the advancement of the damage. e study performed by Mutolo et al [46] on the effects after administration of the same supplement showed significant results only after 6 months of therapy with 2 tablets a day.…”
Section: Journal Of Ophthalmologymentioning
confidence: 93%